Supergroup F Wolbachia in terrestrial isopods Horizontal transmission from termites? - Zimmermann, Bianca Laís (Evolutionary ecology, 2021)
© The Author(s), under exclusive licence to Springer Nature Switzerland AG part of Springer Nature 2021.